Laser-welded connections for high-power electronics in mobile systems - Weigl, M.; Grimm, A.; Schmidt, Michael (1st International Electric Drives Production Conference 2011, EDPC-2011 - Proceedings, 2011)
Laser welding of direct copper-aluminum connections typically leads to the formation of intermetallic phases and an embrittlement of the metal joints. Considering mobile systems such an embrittlement reduces the durability against temperature cycling as well as against dynamic load significantly and limits the overall long-term stability. By means of adapted filler materials it is possible to reduce the brittle phases and thereby enhance the ductility of these dissimilar connections. As the element silicon features quite a well compatibility with copper and aluminum, filler materials based on Al-Si and Cu-Si alloys are used in the current research studies. In contrast to direct Cu-Al welds, the aluminum filler alloy AlSi12 effectuates a more uniform element mixture and a significantly enhanced ductility. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: dissimilar connection; ductility; Laser; welding